Entre convergences et divergences : la communauté haïtienne de Montréal - Ariane Cyr (Anglophonia)
In Canada, multiculturalism which was officially adopted in 1971 has been debated for several years, mainly as regards the consequences of excessive pluralism and the free expression of ethnic differences on the national cohesion and on the coherence of citizenship. Is ethnic divergence compatible with social convergence? Could this association lead to a more productive definition of a multicultural Canada and unveil a new conception of Americanness? Beyond a traditional geographic or monocultural meaning, the notion of Americanness could be regarded today, in a pluralistic context, as an identity duality, as a compromise between distinction and borrowing. The perceptions of the Haitian community of Montreal as regards its adoptive country (Canada, Quebec and Montreal) were useful to specify this new definition. As regards the elements of discourse gathered during individual interviews conducted with the members of the first generation of Haitian immigrants, an identity pattern can be observed, matching two different and yet complementary systems of functioning: detachment and symbolic recognition